An evaluation of late attenders in labour in Alexandra - L. Ngatane; P. Ferrinho; A. McKenzie; S.G. Reinach (AOSIS, 1992)
To study why women present in late labour we interviewed 70 parturients in our labour worn for a period of 8 days in March 1990.